SISTEM INFORMASI ARSIP BERKAS PERKARA PIDANA UMUM KEJAKSAAN NEGERI PALANGKA RAYA - Erfan, Muhammad; Fares, Muhammad Rifki Al; Denada, Denada; Susila, Rani; Nathaniel, Noah Ivander; Ehong, Ehong; Destry, Destry (JUSTIFY : Jurnal Sistem Informasi Ibrahimy, 2025)
Case files are very important documents in the Palangka Raya District Attorney's Office which currently still applies conventional systems such as writing a combination of letters and numbers on physical archive files using Microsoft Excel. The unorganized archive storage space and the large number of case files that have not been computerized cause employees to have difficulty finding the case files when needed by the Prosecutor. This study aims to design and build a general criminal case file archiving system at the Kejaksaan Negeri Palangka Raya. This information system is made web-based using PHP language and MySQL database to replace the existing manual archiving method. Based on the results of the questionnaire responses, 82.5% of this system provides convenience in archiving and retrieving general criminal case files needed by the Prosecutor.